Sintese de catalisadores à base de cobre e ferro suportados em nanotubos de carbono e sua aplicação na reação de oxidação preferencial de CO - Xavier, Juliana da Silva (2018)
Herein, copper (Cu) and iron (Fe) monometallic, and copper-iron (Cu-Fe) bimetallic catalysts supported on functionalized carbon nanotubes (FCNT) were prepared by wet impregnation method. The catalysts were characterized by thermogravimetric analysis (TGA), X-ray diffraction (XRD). N2 physisorption. RAMAN spectroscopy. scanning electron microscopy (SEML X-ray photoelectron spectroscopy (XPS) temperature-programmed reduction (TPR) and temperature-programmed superficial reaction (TPSR). Characterization results indicated that the oxidative treatment applied to the carbon nanotubes was not efficient, since the FCNT presented a low surface area. XRD, TPR and XPS results confi1111ed the presence of CuO and Fe201 phases in the catalysts. The catalysts were evaluated in carbon monoxide preferential oxidation reaction (PROX-CO). All catalysts presented a low CO conversion, and were more selective to hydrogen oxidation reaction. Stability tests have shovm that the catalysts were stable for 20 h at 300 °C.